Dependence of the Productive Properties of Cows of the Simmental Breed on Body Types - Khairullaeva M.Sh; Ochilov O.K; Isaev. A. M; Sattarov F.R (Genius Journals, 2022)
Studies have revealed that the level of milk productivity, the nature of the course of lactation, the yield of dairy products for every 100 kg of live weight and the level of payment for feed with dairy products of Simmental cows are interrelated with body types. In dairy-type cows, the milk yield per lactation is 672.5 and 958.5 kg, 4% milk is 507.4 and 735.4 kg higher, the milk yield for every 100 kg of live milk weight is 164.9 and 228.7 kg higher than that of peers of the milk-meat and meat-dairy types. The highest monthly yield in dairy-type cows was noted in the third, in cows of milk-meat and meat-dairy types in the second month of lactation. This indicates that in dairy cows lactation proceeded more equally than in peers of other types. The data obtained indicate the high efficiency of using dairy-type cows for milk production
Keywords: noted; cows; milk; peers